2008
DOI: 10.1155/2008/209830
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 7-O-Modified Formononetin Derivatives

Abstract: Three series of novel formononetin derivatives were synthesized, in which formononetin and heterocyclic moieties were separated by 2-carbon, 3-carbon, and 4-carbon spacers. The chemical structures of these compounds were confirmed. All the derivatives were screened for antiproliferative activities against Jurkat cell line and HepG-2 cell line. In this paper, compounds prepared were also screened for their antibacterial activity of six bacterial strains. Compound3bexihibited promising antibacterial activity aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These estrogenic metabolites also possess anticancer properties, such as inducing cell apoptosis (Jin et al, 2010; Zongliang et al, 2016). In this regard, several studies also designed and synthesized a series of novel formononetin derivatives or analogues exerting interesting anticancer properties (Yang et al, 2008; Ren et al, 2012; Fu et al, 2017; Lin et al, 2017).…”
Section: Overview Of Formononetinmentioning
confidence: 99%
“…These estrogenic metabolites also possess anticancer properties, such as inducing cell apoptosis (Jin et al, 2010; Zongliang et al, 2016). In this regard, several studies also designed and synthesized a series of novel formononetin derivatives or analogues exerting interesting anticancer properties (Yang et al, 2008; Ren et al, 2012; Fu et al, 2017; Lin et al, 2017).…”
Section: Overview Of Formononetinmentioning
confidence: 99%
“…Yang et al reported the antimicrobial effects of FMN against Gram-positive and Gram-negative bacteria, e.g., Enterobacter cloacae, Escherichia coli, and Pseudomonas aeruginosa (22). Wang et al revealed the antiviral effects of FMN on enterovirus-51, whereas this fraction reduced enterovirus-51 RNA and protein synthesis (23).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the antileishmanial effects of a number of flavones-rich compounds, e.g., luteolin, 7,8-dihydroxyflavone, rhamnetin, 3-hydroxyflavone, catechol, 7,8,3′,4′-tetrahydroxyflavone, and apigenin against L. amazonensis L. donovani, and L. tropica have been reported (21,22). A review reported the potent antimicrobial effects of 7HMI against Staphylococcus aureus, S. aureus, S. epidermidis, Pseudomonas aeruginosa, Candida albicans, C. tropicalis, Cryptococcus neoformans, and enterovirus-51 viruses (23)(24)(25). A previous stud also reported that 7HMI significantly repressed the attachment, flagellar motility, and viability of Giardia trophozoites in mice (26).…”
Section: Discussionmentioning
confidence: 99%